1995
DOI: 10.1063/1.49069
|View full text |Cite
|
Sign up to set email alerts
|

A high gain energy amplifier operated with fast neutrons

Abstract: Design and adaptation of a novel supercritical extraction facility for operation in a glove box for recovery of radioactive elements Rev. Sci. Instrum. 81, 094101 (2010) Silica coated magnetic nanoparticles for separation of nuclear acidic waste J. Appl. Phys. 107, 09B520 (2010) Nuclear waste disposal-pyrochlore (A2B2O7): Nuclear waste form for the immobilization of plutonium and "minor" actinides J. Appl. Phys. 95, 5949 (2004) Nuclear waste disposal-pyrochlore (A2B2O7): Nuclear waste form for the immobiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(50 citation statements)
references
References 4 publications
0
48
0
2
Order By: Relevance
“…The aim of the n TOF project is the measurement of cross sections needed for the design of innovative ADS applications like incineration of nuclear waste [4,5], energy production [6,7], radioisotope production for medical applications [8] and basic science subjects, in particular astrophysics [1]. As a result of the studies reported in a first paper [2] and an addendum [3], the neutron time of flight facility has been proposed at the CERN PS [9] delivering a maximum intensity of 3 × 10 13 protons within a 14.4 s supercyle at a momentum of 20 GeV/c.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the n TOF project is the measurement of cross sections needed for the design of innovative ADS applications like incineration of nuclear waste [4,5], energy production [6,7], radioisotope production for medical applications [8] and basic science subjects, in particular astrophysics [1]. As a result of the studies reported in a first paper [2] and an addendum [3], the neutron time of flight facility has been proposed at the CERN PS [9] delivering a maximum intensity of 3 × 10 13 protons within a 14.4 s supercyle at a momentum of 20 GeV/c.…”
Section: Introductionmentioning
confidence: 99%
“…Among fast spectrum systems some distinct safety superiority is shown by the pool type ones cooled with liquid Pb (Rubbia, 1995) or Pb}Bi eutectics, since their thermal properties exclude a core melt. The roots of the idea of Pb-cooled reactor (Adamov et al, 1991) descend from Pb}Bi Russian submarine propulsion units.…”
Section: Realisationmentioning
confidence: 99%
“…A subcritical nuclear system based on U-Th cycle and fed by a high intensity proton accelerator can be used for energy production and for the transmutation of MAs and LLFP. Later on, the technical feasibility and verification of the principle of energy amplification were investigated [1][2][3][4]. An accelerator-driven sub-critical system (ADS) includes a proton accelerator, an external neutron source generator and a sub-critical system.…”
mentioning
confidence: 99%